Distributed Lock with Inter-core Passing for SW26010 Processor - LI Ming-liang, PANG Jian-min, YUE Feng (Jisuanji kexue, 2022)
In parallel programs,a mutual exclusive lock is often used to avoid conflict when accessing shared resources.The SW26010 processor,which is deployed on the Sunway TaihuLight supercomputer,is a heterogeneous many-core processor and there is no hardware lock mechanism for the co-processing cores.Developers have developed a software lock mechanism based on atomic instructions,but the software lock will lead to significant overhead and affect the performance of parallel programs.To solve this issue,the HDT-LOCK designed as distributed lock mechanism with inter-core passing is proposed.Firstly,the hybrid distributed lock is proposed and implemented based on scratchpad memory on co-processing cores to mitigate memory congestion.Furthermore,the inter-core passing mechanism using register communication and the single-instruction multiple-data instruction is developed to improve the throughput of HDT-LOCK.Experimental results show that the proposed HDT-LOCK mechanism mitigates memory congestion,and has better scalability.In addition,the lock passing mechanism improves HDT-LOCK throughput up to 5.6X.